Peningkatan kemampuan pemahaman matematis peserta didik melalui metode inkuiri model Alberta - Depi Setialesmana (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
This research aimed to observe (1) the improvement of mathematical understanding of students who were taught with Alberta inquiry method compared to conventional method, (2) the differences in improvement of mathematical understanding of students with higher, moderate and lower of mathematical abilities who had learning process with Alberta inquiry method and conventional method, and (3) attitudes of students after learning using Alberta inquiry method. Population in this research were all grade VIII students at Junior High School 12 Tasikmalaya Two classes were selected as the samples. One class was selected as the experiment class and the other served as the control class. The instruments used consisted of understanding skill test and attitudes scale questionnaire. Data processing technique used “normalized gain test“, t-test, Two-way ANOVA. The results showed that the improvement of mathematical understanding and mathematical critical thinking of the students who learned using Alberta Inquiry method were better than this learnd using conventional method. There were differences between the improvement of mathematical understanding of students, with higher, moderate and lower mathematical abilities who learned using Alberta inquiry method compared to there learned using conventional method. Students showed a positive attitude toward learning process using, Alberta inquiry method.